2006
DOI: 10.1029/2006gl026239
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated drawdown of meridional overturning in the late‐glacial Atlantic triggered by transient pre‐H event freshwater perturbation

Abstract: Abrupt decreases of the Atlantic meridional overturning circulation (MOC) during the Late Pleistocene have been directly linked to catastrophic discharges of glacimarine freshwater, triggering disruption of northward marine heat transport and causing global climate changes. Here we provide measurements of excess sedimentary 231Pa/230Th from a high‐accumulation sediment drift deposit in the NE Atlantic that record a sequence of sudden variations in the rate of MOC, associated deep ocean ventilation and surface‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 36 publications
7
115
0
2
Order By: Relevance
“…The strong increase of the 'Fleuve Manche' activity from ca. 18.3 ka occurred at time of important environmental changes in the north and north-western British ice margin (Knutz et al, 2002a;Knutz et al, 2002b;Wilson et al, 2002;Hall et al, 2006), contemporaneous with the maximum decay of the FIS (Svendsen et al, 1996;Kleiber et al, 2000;Vorren and Plassen, 2002;Dahlgren and Vorren, 2003;Nygard et al, 2004;Lekens et al, 2005;Knies et al, 2007;Rinterknetch et al, 2007;Goehring et al, 2008), reinforcing the idea that the 'Fleuve Manche' activity was strongly dependent on the surrounding ice-sheet runoff. As a result, the 'Fleuve Manche' was a glacially-fed river and the Bay of Biscay was a depocentre for the European ice sheets erosional products, whose accumulations are still widely visible all along the southern margins of the past FIS (Eissmann, 2002;Houmark-Nielsen and Kjaer, 2003; and BIIS (Eyles and McCabe, 1989;Bowen et al, 2002;Evans and O'Cofaigh, 2003).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The strong increase of the 'Fleuve Manche' activity from ca. 18.3 ka occurred at time of important environmental changes in the north and north-western British ice margin (Knutz et al, 2002a;Knutz et al, 2002b;Wilson et al, 2002;Hall et al, 2006), contemporaneous with the maximum decay of the FIS (Svendsen et al, 1996;Kleiber et al, 2000;Vorren and Plassen, 2002;Dahlgren and Vorren, 2003;Nygard et al, 2004;Lekens et al, 2005;Knies et al, 2007;Rinterknetch et al, 2007;Goehring et al, 2008), reinforcing the idea that the 'Fleuve Manche' activity was strongly dependent on the surrounding ice-sheet runoff. As a result, the 'Fleuve Manche' was a glacially-fed river and the Bay of Biscay was a depocentre for the European ice sheets erosional products, whose accumulations are still widely visible all along the southern margins of the past FIS (Eissmann, 2002;Houmark-Nielsen and Kjaer, 2003; and BIIS (Eyles and McCabe, 1989;Bowen et al, 2002;Evans and O'Cofaigh, 2003).…”
Section: Resultsmentioning
confidence: 83%
“…For the last glacial period, the huge 'Fleuve Manche' discharges dating from ca. 18 ka correlate with significant freshwater fluxes from the circum-North Atlantic ice sheets, as reported from the FIS (Kleiber et al, 2000;Dahlgren and Vorren, 2003;Lekens et al, 2005;Rasmussen et al, 2007), the BIIS (Zaragosi et al, 2001;Hall et al, 2006;Ménot et al, 2006;Toucanne et al, 2008) and the LIS (Clarke et al, 1999;Tripsanas and Piper, 2008), indicating that the 'Fleuve Manche' activity reflected a large-scale event of meltwater releases. Geochemical and isotopical data from numerous cores from the North Atlantic show a sharp concomitant decrease in the rate of deep-water formation leading to the HE 1 and a collapsed THC until ca.…”
Section: Comments On the Timing Of Major 'Fleuve Manche' Discharges Amentioning
confidence: 70%
See 1 more Smart Citation
“…Previous studies have documented a strong relationship between sedimentary composition, specifically opal content, and the 231 Pa/ 230 Th ratio in both sediment traps 17 and downcore records [22][23][24] . Some authors have sought to minimize the effects of scavenging by excluding diatom-rich intervals 25 or high-flux sites, where 231 Pa/ 230 Th and opal flux correlate the most strongly 20 . We do not exclude any data from our 25-core depth survey; instead we use opal and particle fluxes to ascertain how much of the observed difference between our time periods may be due to changes in mass flux or opal flux ( Supplementary Figs 2-5 Supplementary Fig.…”
Section: Spatiomentioning
confidence: 99%
“…McManus et al (2004) suggested a near total collapse of Atlantic MOC during Heinrich event 1 based on a sedimentary Pa/Th record from the Bermuda Rise. However, since the adsorbed sedimentary Pa/Th signal is also highly sensitive to particle compositions (biogenic silica content) such an interpretation has to be treated with caution and Atlantic MOC reduction may not have been so severe (Chase et al, 2002;Hall et al, 2006;Keigwin and Boyle, 2008;Gherardi et al, 2009;Lippold et al, 2009). In addition, several of the major Heinrich IRD discharge events (H1, H2, H4) were apparently accompanied by meltwater precursor events originating from the Northwest European Ice Sheet (NWEIS) suggesting that ice sheet collapse of European origin may have pre-conditioned the MOC in the North Atlantic (Peck et al, 2007b).…”
Section: Climate and Hydrographymentioning
confidence: 99%